DISTRIBUSI DAN SIKLUS NUTRIENT DI PERAIRAN ESTUARI SERTA PENGENDALIANNYA - Deny Yogaswara (OSEANA, 2020)
Nutrient components (consist of nitrogen and phosphorus) are needed for healthy ecosystems and they are naturally widespread throughout the aquatic and terrestrial environment. Nutrient loading as a result of anthropogenic activities comes from rivers that flow into the estuary. The abundance and the cycles of nutrients in the estuary are affected by physical factors (i.e. hydrodynamic conditions such as currents and tides, turbidity and waves), biological factors (i.e. filter feeder organism) and chemical factors (i.e. material fixation and decomposition). To supporting estuarine food webs, phytoplankton and primary productivity are fundamental importance. Besides, they are also key drivers of biogeochemical cycling and play a central role in determining water quality. But on the contrary, within the same conditions, it has negative impact on the estuary environment. The negative impact of high primary productivity in the estuary can cause an algae bloom. Algae bloom occurs when abundant nutrients and optimum sunlight intensity, with the lowest current at the same time. Algae bloom has a negative impact on estuary ecosystems because it makes depleting of dissolved oxygen, with the mass death of marine biota such as fish as a consequence. Therefore, the amount of nutrients from anthropogenic activities have to be controlled and monitored before they flow to the river. The method to control the waste is treated in a Waste Water Treatment Plant (WWTP) system. This treatment by using the WWTP system could reduce the concentration of nutrients spread in the estuary and it will prevent the occurrence of algae bloom phenomena.